Concept and Process of Creating Northeastern Folk Music - Direksin, Poowaniy; Nesusin, Surapon (Journal of Fine and Applied Arts Khon Kaen University, 2020)
The objectives of this research were to study the concepts for creating northeastern music and to create one from documents, research and concepts from writers in the past. The researcher considered creating process, methods, concepts and inspirations, as well as, analyzed based on analysis theory of northeastern music, considers benefits from creating, knew about concepts of writer in the past and concepts for developing creation of more various northeastern music. Concepts and inspirations of creating northeastern folk music found that concept from writers in the past had different concepts and inspirations, so did creating process. Each concept was unique for each writer. Inspiration of creating northeastern music found that inspirations of writers in the past were different and had interesting dominant, for example, inspirations from lifestyle, culture, tradition, society and environment, imitating nature, imitating animals, which writers wrote it from their experiences, seeing, listening, observation and living. Process of creating found that writers in the past had many similar processes, which are, creating format, melody and rhythm, by starting to create differently. Some started with melody, some started with determining format of music by considering suitability of melody, rhythm and format that correlate with concept and inspiration to get perfect music. But in the past, there was no note, so melody, rhythm and format of music were recorded by remembering and following player, listening and remembering to play different northeastern musical instruments. For creating new northeastern music, the researcher had studied concepts and inspirations, including process of creating northeastern music from writers in the past. The concept of creating single of local northeastern musical instruments of Pong Lang using inspiration, concept and creating process based on local music analysis and creating according to inspiration of the researcher and hope that new single Pong Lang created this time will help with skills in writing local northeastern music, playing and technique. The researcher hoped learners of this research can use knowledge to benefit education of theory and it will be a guideline to preserve local northeastern music in the community and country.